Clinical outcomes after shared decision‐making tools with families of children with obstructive sleep apnea without tonsillar hypertrophy. (7th January 2019) - Bergeron, Mathieu; Duggins, Angela; Chini, Barbara; Ishman, Stacey L.
Abstract : Objectives: To determine if shared decision‐making tools (SDMTs) improve clinical outcomes for these children. Shared decision making (SDM) is a collaborative process in which patients and clinicians jointly establish treatment plans that integrate clinical evidence and patient values/preferences. We previously reported less decisional conflict using a SDMT for families of children with obstructive sleep apnea (OSA) without tonsillar hypertrophyl; however, the clinical impact of this finding is unknown. Methods: Prospective single‐blind randomized controlled trial for consecutive patients referred to a multidisciplinary upper airway center. The study group used a SDMT, whereas the control group did not; all were followed until their next appointment and polysomnogram. Results: We assessed 50 families (24 study, 26 controls); mean age of patients was 8.8 (95% confidence interval 6.9–10.6) years, and 44% were female. After their initial visit, there was agreement between families and providers on the best treatment option for 22 of 24 (91.7%) study patients and 12 of 26 (46.2%) controls ( P < 0.001). Before the first follow‐up, four control families (15.4%) modified their treatment plan, whereas none of the study families did so ( P = 0.04). Continuous positive airway pressure (CPAP) compliance was 27% (3 of 11) for controls and 57% (5 of 8) for study patients ( P = 0.11). The median obstructive apnea‐hypopnea index significantly improved in study patients from 13.4 (range, 20.0–57.2) to 3.5 (range 0.4–45.5, P = 0.01] events per hour, but not in controls, with 9.4 (range, 0.9–76.2) to 4.9 (range, 0–116, P = 0.10) events per hour. Conclusion: Families of children with OSA without tonsillar hypertrophy who were counseled regarding treatment options using SMDTs were more likely to undergo agreed upon treatment and had higher CPAP compliance. Level of Evidence: 1b. Laryngoscope, 129:2646–2651, 2019